Difunctional composite material as well as preparation method and application thereof
By using a dual-function composite material composed of magnetic biochar carrier, quaternized chitosan and cationic polyacrylamide, efficient removal and rapid recovery of water microplastics are achieved, and the problems of unsatisfactory removal rate and low recycling efficiency in the prior art are solved.
Patent Information
- Application Number
- CN202411706980.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When removing water microplastics, the prior art has a long settlement time, an unsatisfactory removal rate, and a small adsorption capacity, making it difficult to achieve a fast and efficient removal effect.
Using a dual-function composite material consisting of magnetic biochar carrier, quaternized chitosan and cationic polyacrylamide, the microplastics are removed by dual functions of adsorption and flocculation, and the material is quickly recovered by magnetic separation.
It has achieved efficient removal of microplastics in water, with a removal rate of more than 97.27%. It also quickly recovers materials through magnetic separation, which is simple to operate and has high recycling efficiency.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water microplastic treatment, and specifically relates to a dual-functional composite material and a preparation method and application thereof. Background Art
[0002] Microplastics refer to plastic fragments and particles with a diameter of less than 5 mm. They are a mixture of non-uniform plastic particles of various shapes that are often difficult to distinguish with the naked eye.
[0003] The removal method of microplastics in water is mainly based on flocculation and sedimentation. For example, patent CN118108354A discloses using trivalent iron salts or trivalent aluminum salts as flocculants to regulate the pH value of the water body, promote the hydrolysis of trivalent iron ions or trivalent aluminum ions to form chain and network polyhydroxide floccules, and remove micro-nano plastics in the water body through bridging or netting flocculation. Patent CN111018065A discloses using aluminum sulfate or calcium oxide as flocculants to treat microplastic acrylic copolymers in water. Patent CN114590880A discloses using polyaluminum chloride while using anionic polyacrylamide or non-ionic polyacrylamide as a coagulant. However, the above-mentioned prior art has a long sedimentation time and an unsatisfactory removal rate, and a small amount of microplastics still remain in the water. The physical adsorption method has a short adsorption time, which makes up for some of the shortcomings of the flocculation sedimentation method. For example, patent CN118616029A discloses a metal-modified porous adsorbent of activated carbon loaded with metal oxide or metal hydroxide nanoparticles, but its removal rate of microplastics is limited to 94%, and it cannot achieve a higher removal rate, and the adsorbent cannot be quickly separated from the water body after adsorption. For another example, patent CN117902664A discloses a lignin carbon-based magnetic adsorption material, which improves the separation characteristics of the adsorption material, but the adsorption capacity of the adsorption material is small.
[0004] Therefore, how to quickly and efficiently remove microplastics from water is an urgent problem that needs to be solved. Summary of the invention
[0005] In order to solve the technical problems of long sedimentation time, unsatisfactory removal rate and small adsorption capacity in the prior art, a composite material with dual functions of adsorption and flocculation and a preparation method and application thereof are provided.
[0006] The present invention adopts the following technical solution:
[0007] A method for preparing a dual-functional composite material comprises the following steps:
[0008] Step 1, mixing microcrystalline cellulose, iron salt and water to obtain iron salt modified microcrystalline cellulose;
[0009] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a protective atmosphere to obtain magnetic biochar;
[0010] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution to obtain modified biochar;
[0011] Step 4, the modified biochar, acrylamide monomer, cationic monomer and water are mixed, nitrogen is introduced to remove oxygen, and then an initiator and an auxiliary agent are added to carry out a polymerization reaction under closed conditions to obtain a dual-functional composite material.
[0012] The present invention uses microcrystalline cellulose as a biomass raw material, and the magnetic biochar carrier obtained by carbonization has a stable porous carbon structure and a large specific surface area, which provides a basis for the loading of quaternized chitosan and polyacrylamide. In addition, the magnetic biochar carrier and quaternized chitosan have high adsorption performance, and the quaternized chitosan has been quaternized compared to chitosan and has positive charge, and the microplastics are fixed on the composite material through physical adsorption and electrostatic action.
[0013] Preferably, the ratio of microcrystalline cellulose to iron salt in step 1 is (1-10) g: (1-15) mmol.
[0014] Preferably, the pyrolysis temperature in step 2 is 600-800° C.; the pyrolysis time is 1-3 h.
[0015] Preferably, in step 3, the usage ratio of the magnetic biochar and the quaternized chitosan solution is (1-5) g: (100-200) mL; the immersion temperature is 60-120° C.; and the immersion time is 30-60 min.
[0016] Preferably, the mass ratio of the modified biochar, acrylamide monomer, cationic monomer, initiator and auxiliary agent in step 4 is (10-20): (1-30): (1-10): (0.001-1): (0.1-2).
[0017] Preferably, the cationic monomer in step 4 is dimethyldiallylammonium chloride or acryloyloxyethyltrimethylammonium chloride.
[0018] The positively charged functional groups in the cationic monomers remove microplastics through flocculation, and the cationic monomers further enhance the electrostatic effect of quaternized chitosan by providing more positive charges.
[0019] Preferably, the initiator in step 4 is one or both of ammonium persulfate and azobisisobutylamidine hydrochloride.
[0020] Preferably, the polymerization reaction temperature in step 4 is 30-80° C.; and the polymerization reaction time is 5-10 h.
[0021] A dual-functional composite material is prepared by the above preparation method.
[0022] Application of a bifunctional composite material in treating microplastics in water bodies.
[0023] The beneficial effects of the present invention are:
[0024] The composite material prepared by the method of the present invention uses magnetic biochar as a carrier, on which quaternized chitosan and cationic polyacrylamide are loaded, and has dual functions of adsorption and flocculation. After adsorption and flocculation, the composite material can also be separated by magnetism, and the formed flocs are large, so the material can be quickly and efficiently recovered, the operation is simple, and the recovery efficiency is high. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and technical effect of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments.
[0026] Embodiment 1:
[0027] A dual-functional composite material, the preparation method of which comprises the following steps:
[0028] Step 1, mixing microcrystalline cellulose, ferric nitrate nonahydrate and water in a ratio of 1 g: 1 mmol: 50 g, stirring at 40° C. for 30 min, and then separating, and drying the product at 120° C. for 8 h to obtain iron salt-modified microcrystalline cellulose;
[0029] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a nitrogen atmosphere at a temperature of 600° C. for 1 h to obtain magnetic biochar;
[0030] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution (the concentration of chitosan is 15 g / L, the concentration of citric acid is 1 g / L), the amount ratio of the magnetic biochar to the quaternary ammonium chitosan solution is 1 g: 100 mL, the immersion temperature is 90°C, the time is 30 min, and the immersion is separated after the immersion is completed, and the product is dried at 80°C for 8 h to obtain modified biochar;
[0031] Step 4, the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride and water are mixed, nitrogen is introduced for deoxygenation for 20 minutes, and then ammonium persulfate and disodium ethylenediaminetetraacetate are added. The mass ratio of the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride, ammonium persulfate, disodium ethylenediaminetetraacetate and water is 10:1:1:0.001:0.1:50. The polymerization reaction is carried out at 30°C under closed conditions for 5 hours. After the polymerization reaction is completed, the product is dried and crushed to obtain a dual-functional composite material.
[0032] 10 mg of the bifunctional composite material prepared above was added to 100 mL, 100 mg / L PVC microplastic solution, and the solution was kept at a constant temperature of 25°C and 200 rpm for 12 hours. After the separation, magnetic separation was performed and the concentration of the remaining microplastics in the supernatant was determined by fluorescence spectroscopy (obtained by substituting the fluorescence intensity into the standard curve) to be 2.73 mg / L. The removal rate was calculated to be 97.27%.
[0033] Embodiment 2:
[0034] A dual-functional composite material, the preparation method of which comprises the following steps:
[0035] Step 1, mixing microcrystalline cellulose, ferric nitrate nonahydrate and water in a ratio of 3 g:5 mmol:60 g, stirring at 50° C. for 40 min, and then separating, and drying the product at 120° C. for 8 h to obtain iron salt-modified microcrystalline cellulose;
[0036] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a nitrogen atmosphere at a temperature of 650° C. for 1 h to obtain magnetic biochar;
[0037] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution (the concentration of chitosan is 18 g / L, the concentration of citric acid is 4 g / L), the amount ratio of the magnetic biochar to the quaternary ammonium chitosan solution is 2 g: 120 mL, the immersion temperature is 90° C., the time is 40 min, and after the immersion is completed, the product is separated and dried at 80° C. for 8 h to obtain modified biochar;
[0038] Step 4, the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride and water are mixed, nitrogen is introduced for deoxygenation for 30 minutes, and then ammonium persulfate and disodium ethylenediaminetetraacetate are added. The mass ratio of the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride, ammonium persulfate, disodium ethylenediaminetetraacetate and water is 13:10:2:0.1:0.5:70. The polymerization reaction is carried out at 40°C under closed conditions for 6 hours. After the polymerization reaction is completed, the product is dried and crushed to obtain a dual-functional composite material.
[0039] The method for treating microplastics in water using the bifunctional composite material prepared above is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 2.01 mg / L, and the removal rate is 97.99%.
[0040] Embodiment 3:
[0041] A dual-functional composite material, the preparation method of which comprises the following steps:
[0042] Step 1, mixing microcrystalline cellulose, ferric nitrate nonahydrate and water in a ratio of 5 g:10 mmol:80 g, stirring at 60° C. for 50 min, and then separating, and drying the product at 120° C. for 8 h to obtain iron salt-modified microcrystalline cellulose;
[0043] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a nitrogen atmosphere at a temperature of 700° C. for 2 h to obtain magnetic biochar;
[0044] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution (the concentration of chitosan is 20 g / L, the concentration of citric acid is 6 g / L), the amount ratio of the magnetic biochar to the quaternary ammonium chitosan solution is 3 g: 150 mL, the immersion temperature is 100 ° C, the time is 50 min, and the immersion is separated after the immersion is completed, and the product is dried at 80 ° C for 8 h to obtain modified biochar;
[0045] Step 4, the modified biochar, acrylamide monomer, acryloyloxyethyltrimethylammonium chloride and water are mixed, nitrogen is introduced for deoxygenation for 50 minutes, and then azobisisobutylamidine hydrochloride and disodium ethylenediaminetetraacetate are added. The mass ratio of the modified biochar, acrylamide monomer, acryloyloxyethyltrimethylammonium chloride, azobisisobutylamidine hydrochloride, disodium ethylenediaminetetraacetate and water is 15:15:4:0.5:1:100. The polymerization reaction is carried out at 60°C under closed conditions for 7 hours. After the polymerization reaction is completed, the product is dried and crushed to obtain a dual-functional composite material.
[0046] The method for treating microplastics in water using the bifunctional composite material prepared above is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 1.86 mg / L, and the removal rate is 98.14%.
[0047] Embodiment 4:
[0048] A dual-functional composite material, the preparation method of which comprises the following steps:
[0049] Step 1, mixing microcrystalline cellulose, ferric nitrate nonahydrate and water in a ratio of 8 g:10 mmol:100 g, stirring at 80° C. for 60 min, and then separating, and drying the product at 120° C. for 8 h to obtain iron salt-modified microcrystalline cellulose;
[0050] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a nitrogen atmosphere at a temperature of 720° C. for 3 h to obtain magnetic biochar;
[0051] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution (the concentration of chitosan is 22 g / L, the concentration of citric acid is 9 g / L), the amount ratio of the magnetic biochar to the quaternary ammonium chitosan solution is 3 g:160 mL, the immersion temperature is 100 ° C, the time is 50 min, and the immersion is separated after the immersion is completed. The product is dried at 100 ° C for 10 hours to obtain modified biochar;
[0052] Step 4, the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride and water are mixed, nitrogen is introduced for deoxygenation for 60 minutes, and then ammonium persulfate and disodium ethylenediaminetetraacetate are added. The mass ratio of the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride, ammonium persulfate, disodium ethylenediaminetetraacetate and water is 17:25:6:0.7:0.5:150. The polymerization reaction is carried out at 60°C under closed conditions for 8 hours. After the polymerization reaction is completed, the product is dried and crushed to obtain a dual-functional composite material.
[0053] The method for treating microplastics in water using the bifunctional composite material prepared above is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 0.89 mg / L, and the removal rate is 99.11%.
[0054] Embodiment 5:
[0055] A dual-functional composite material, the preparation method of which comprises the following steps:
[0056] Step 1, mixing microcrystalline cellulose, ferric nitrate nonahydrate and water in a ratio of 10 g: 15 mmol: 100 g, stirring at 90° C. for 90 min, and then separating, and drying the product at 120° C. for 8 h to obtain iron salt-modified microcrystalline cellulose;
[0057] Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a nitrogen atmosphere at a temperature of 800° C. for 3 h to obtain magnetic biochar;
[0058] Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution (the concentration of chitosan is 25 g / L, the concentration of citric acid is 10 g / L), the amount ratio of the magnetic biochar to the quaternary ammonium chitosan solution is 5 g: 200 mL, the immersion temperature is 110° C., the time is 60 min, and the immersion is separated after the immersion is completed, and the product is dried at 120° C. for 16 h to obtain modified biochar;
[0059] Step 4, the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride and water are mixed, nitrogen is introduced for deoxygenation for 90 minutes, and then ammonium persulfate and disodium ethylenediaminetetraacetate are added. The mass ratio of the modified biochar, acrylamide monomer, dimethyldiallyl ammonium chloride, ammonium persulfate, disodium ethylenediaminetetraacetate and water is 20:30:10:1:2:200. The polymerization reaction is carried out at 80°C under closed conditions for 10 hours. After the polymerization reaction is completed, the product is dried and crushed to obtain a dual-functional composite material.
[0060] The method for treating microplastics in water using the bifunctional composite material prepared above is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 1.21 mg / L, and the removal rate is 98.79%.
[0061] Based on Example 1, the present invention changes the pyrolysis conditions in step 2 to study the effects of different pyrolysis conditions on the specific surface area of magnetic biochar. The results are shown in Table 1:
[0062] Table 1 Effect of different pyrolysis conditions on the specific surface area of magnetic biochar
[0063] Pyrolysis temperature℃ Pyrolysis time h <![CDATA[Specific surface area m 2 / g]]> <![CDATA[Pore volume m 3 / g]]> 600 1 653 0.312 600 2 679 0.361 600 3 758 0.373 720 1 688 0.354 720 2 692 0.366 720 3 735 0.389 800 1 727 0.403 800 2 785 0.428 800 3 820 0.457 850 1 842 0.477 850 2 858 0.481 850 3 861 0.479 900 1 879 0.484 900 2 886 0.472 900 3 882 0.478
[0064] Based on Example 1, the present invention changes the immersion conditions in step 3 to study the effects of different immersion conditions on the removal rate of microplastics. The results are shown in Table 2 below:
[0065] Table 2 Effect of different immersion conditions on microplastic removal rate
[0066] Dipping temperature ℃ Dipping time min Removal rate % 25 10 82.3 25 30 86.7 25 60 94.5 25 90 98.2 25 150 99.4 50 10 85.8 50 30 89.6 50 60 92.7 50 90 98.4 50 150 98.9 80 10 85.2 80 30 89.1 80 60 96.7 80 90 98.8 80 150 99.7 150 10 95.3 150 30 98.2 150 60 99.6 150 90 99.7 150 150 99.9 200 10 97.5 200 30 98.4 200 60 99.7 200 90 99.8 200 150 99.9
[0067] Based on Example 1, the present invention studies the effect of the initial concentration of the PVC microplastic solution on the microplastic removal rate. The dosage of the dual-functional composite material in Example 1 is 20 mg, the volume of the PVC microplastic solution is 100 mL, and the constant temperature oscillation time is 12 h. The results are shown in Table 3 below:
[0068] Table 3 Effect of initial concentration of PVC microplastic solution on microplastic removal rate
[0069] Initial concentration mg / L 20 50 70 100 120 Removal rate % 99.9 99.9 99.8 99.7 99.8 Initial concentration mg / L 150 200 250 300 400 Removal rate % 99.4 98.7 97.6 90.9 81.4
[0070] Based on Example 1, the present invention studies the effect of constant temperature oscillation time on the removal rate of PVC microplastics. The dosage of the dual-functional composite material in Example 1 is 20 mg, the volume of the PVC microplastic solution is 100 mL, and the concentration is 100 mg / L. The results are shown in Table 4 below:
[0071] Table 4 Effect of constant temperature oscillation time on the removal rate of PVC microplastics
[0072] Constant temperature oscillation time h 2 4 6 8 10 Removal rate % 42.5 64.7 78.2 88.9 96.1 Constant temperature oscillation time h 12 14 16 20 24 Removal rate % 99.7 99.8 99.7 99.7 99.8
[0073] Based on Example 1, the present invention studies the removal rate of different types of microplastics by the composite material. The dosage of the dual-functional composite material in Example 1 is 20 mg, the volume of the microplastic solution is 100 mL, and the concentration is 100 mg / L. The results are shown in Table 5 below:
[0074] Table 5 Removal rates of different types of microplastics
[0075] Microplastics Initial concentration mg / L Constant temperature oscillation time h Removal rate % PP 100 12 98.6 PS 100 12 99.2 PE 100 12 99.6 PVC 100 12 99.7 PET 100 12 98.9
[0076] Comparative Example 1:
[0077] A composite material, which differs from Example 1 in that the treatment in step (4) is not performed, and the rest is the same as Example 1.
[0078] The method for treating microplastics in water using the composite material prepared above, i.e., modified biochar, is as described in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 9.34 mg / L, and the removal rate is 90.66%.
[0079] Comparative Example 2:
[0080] A composite material, which differs from Example 1 in that the treatment of step (3) is not performed, that is, the magnetic biochar obtained in step 2, acrylamide monomer, dimethyldiallylammonium chloride and water are mixed, and the rest is the same as Example 1.
[0081] The method for treating microplastics in water using the composite material prepared as described above is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 12.58 mg / L, and the removal rate is 87.42%.
[0082] Comparative Example 3:
[0083] A composite material, which differs from Example 1 in that step (3) and step (4) are not performed, and the rest is the same as Example 1.
[0084] The method for treating microplastics in water using the composite material prepared above, namely magnetic biochar, is shown in Example 1. The concentration of remaining microplastics in the supernatant after treatment is 26.16 mg / L, and the removal rate is 73.84%.
[0085] It should be understood that parts not described in detail in this specification belong to the prior art.
[0086] The above are only specific implementation methods and processes of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art should understand that this is only an example, and various changes and substitutions can be made to this implementation method without departing from the essence of the present invention. The scope of the present invention is limited only by the attached claims.
Claims
1. A method for preparing a dual-functional composite material, characterized in that: The following steps are involved: Step 1, mixing microcrystalline cellulose, iron salt and water to obtain iron salt modified microcrystalline cellulose; Step 2, pyrolyzing the iron salt-modified microcrystalline cellulose under a protective atmosphere to obtain magnetic biochar; Step 3, immersing the magnetic biochar in a quaternary ammonium chitosan solution to obtain modified biochar; Step 4, the modified biochar, acrylamide monomer, cationic monomer and water are mixed, nitrogen is introduced to remove oxygen, and then an initiator and an auxiliary agent are added to carry out a polymerization reaction under closed conditions to obtain a dual-functional composite material.
2. The method for preparing a dual-functional composite material according to claim 1, characterized in that: The usage ratio of microcrystalline cellulose and iron salt in step 1 is (1-10) g: (1-15) mmol.
3. The method for preparing a dual-functional composite material according to claim 2, characterized in that: The pyrolysis temperature in step 2 is 600-800° C.; the pyrolysis time is 1-3 h.
4. The method for preparing a dual-functional composite material according to claim 2, characterized in that: In step 3, the usage ratio of the magnetic biochar and the quaternized chitosan solution is (1-5) g: (100-200) mL; the immersion temperature is 60-120° C.; and the immersion time is 30-60 min.
5. The method for preparing a dual-functional composite material according to claim 4, characterized in that: The mass ratio of the modified biochar, acrylamide monomer, cationic monomer, initiator and auxiliary agent in step 4 is (10-20): (1-30): (1-10): (0.001-1): (0.1-2).
6. The method for preparing a dual-functional composite material according to claim 4, characterized in that: The cationic monomer in step 4 is dimethyldiallylammonium chloride or acryloyloxyethyltrimethylammonium chloride.
7. The method for preparing a dual-functional composite material according to claim 6, characterized in that: The initiator in step 4 is one or both of ammonium persulfate and azobisisobutylamidine hydrochloride.
8. The method for preparing a dual-functional composite material according to claim 5, characterized in that: The polymerization reaction temperature in step 4 is 30-80° C.; the polymerization reaction time is 5-10 h.
9. A dual-functional composite material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a dual-functional composite material as claimed in claim 9 in treating microplastics in water.
Citation Information
Patent Citations
Flocculation treatment method of micro-plastic acrylate copolymer in water
CN111018065A
Coagulation water treatment method for removing micro-plastics
CN114590880A
Preparation process of high-solubility high-molecular-weight cationic polyacrylamide
CN114478922A
Modified flocculant as well as preparation method and application thereof
CN114805688A
Water purifying agent for sewage treatment and preparation method thereof
CN117732448A